Competition and innovation in a technology setting software duopoly - Philipp J. H. Schröder; Jürgen Bitzer (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
Recently the software industry has experienced fundamental changes in market structure through the entry of open source competitors, e.g. Linux`s entry into the operating systems market. In a simple model we examine the effects of such a change in market structure from monopoly to duopoly under the assumption that software producers compete in technology rather than price or quantities. The model includes the presence of technological progress and menu costs of adjusting existing software, i.e. innovation. It is found that: (i) moving from monopoly to duopoly does increase the technology level set by firms in the software industry; (ii) a duopoly adjusts more readily to global technological progress than a monopolist. Furthermore, results are presented comparing open source versus for-profit firms in terms of technology levels and innovation.
Keywords: H41; L86; L31; 330; open source software; strategic interaction; duopoly; menu costs; Softwareindustrie; Open Source; Duopol; Innovationswettbewerb; Anpassungskosten; Theorie